Implementation of the Merdeka Curriculum in Learning Supervision for Inclusion Programs in Primary Education - Meyritha Trifina Sari; Dian Yunitasari; Achmad Supriyanto; Kim Leah (Yayasan Cendekiawan Digital Indonesia, 2025)
This community service aims to socialize the implementation of the Merdeka Curriculum for learning supervision in inclusion service programs in education units. The activity involved 2,500 participants, including education supervisors, principals, and teachers in Jombang district. Conducted on April 3, 2024, via Zoom and YouTube Live, the session lasted 90 minutes from 09.00 to 10.30 WIB. The event utilized an interactive dialogue approach, engaging policymakers from the Jombang District Education Office and related agencies. This initiative yielded significant outcomes. First, it enhanced participants' understanding of the importance of learning supervision in inclusion programs, which is crucial for ensuring the optimal implementation of these programs in schools. Second, it initiated plans for subsequent interactive dialogues on supervisory themes in inclusion programs, fostering continued collaboration and knowledge sharing among stakeholders. Moreover, the activity provided actionable recommendations for policy enhancements to strengthen the supervision process, enabling more structured and effective practices in inclusive education. These policy recommendations are expected to address challenges in the field, such as resource allocation, training for educators, and monitoring mechanisms. This community service highlights the critical role of collaboration between policymakers, educators, and schools in advancing inclusive education, thereby supporting the broader goals of equitable access and quality education for all students in the Jombang district.